2012
DOI: 10.1016/j.cancergen.2011.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonality of multifocal epithelioid hemangioendothelioma of the liver by analysis of WWTR1-CAMTA1 breakpoints

Abstract: Like other vascular tumors, epithelioid hemangioendothelioma (EHE) can have multifocal presentation in up to 50% of cases. However, whether multifocal EHE represents an unusual pattern of metastasis or multiple separate primary tumors remains to be elucidated. Our recent identification of WWTR1-CAMTA1 fusion as the genetic hallmark of EHE irrespective of anatomic location was used to clarify this question by comparing the similarity of translocation breakpoints. In our previous study, we found variability of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 19 publications
4
49
0
Order By: Relevance
“…Up to one-half of EHE cases show multifocal presentation even in different locations [10]. Utilizing molecular analysis to understand disease progression, multifocal EHEs probably represent metastatic implants of the primary tumor rather than synchronous multiple tumor clones [10]. Consistent with the above concept, the cecal tumor in our case was considered to be secondary to the hepatic EHE, although the primary tumor tissue was unavailable for molecular analysis.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Up to one-half of EHE cases show multifocal presentation even in different locations [10]. Utilizing molecular analysis to understand disease progression, multifocal EHEs probably represent metastatic implants of the primary tumor rather than synchronous multiple tumor clones [10]. Consistent with the above concept, the cecal tumor in our case was considered to be secondary to the hepatic EHE, although the primary tumor tissue was unavailable for molecular analysis.…”
Section: Discussionsupporting
confidence: 67%
“…Recently, nuclear CAMTA1 expression has been found to be a useful immunohistochemical marker and can distinguish EHE from its histologic mimics [8,9]. Up to one-half of EHE cases show multifocal presentation even in different locations [10]. Utilizing molecular analysis to understand disease progression, multifocal EHEs probably represent metastatic implants of the primary tumor rather than synchronous multiple tumor clones [10].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, by analysis of WWTR1-CAMTA1 breakpoints in multiple nodules from two patients with multifocal hepatic EHE, we were able to prove recently that this phenomenon is monoclonal, representing metastatic implants of the same neoplastic clone rather than a 'field-effect' or synchronous occurrence of multiple neoplastic clones. 13 In a recent study, we identified the presence of YAP1-TFE3 gene fusion in a specific subset of EHE, lacking the WWTR1-CAMTA1 fusion and displaying a somewhat distinct morphology and strong TFE3 expression by immunohistochemistry. 14 YAP1 transcriptional co-activator is a major downstream effector of the Hippo pathway and shares significant functional and sequence homology with WWTR1.…”
Section: Geneticsmentioning
confidence: 90%
“…1C; Supplemental Table S3). CAMTA1 has been reported to act as a tumor suppressor gene in gliomas (Henrich et al 2011) and to fuse with WWTR1 in hemangioendotheliomas (Errani et al 2012). FAF1 is adjacent to the tumor suppressor CDKN2C.…”
Section: Faf1 Is a Putative Tumor Suppressor Gene In Gbmmentioning
confidence: 99%